2017
DOI: 10.1111/opo.12356
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation and pupil behaviour of binocularly viewing early presbyopes

Abstract: Purpose: To study accommodation behaviour of early presbyopes with the full suite of accommodative stimuli, and to monitor changes in spherical aberration, pupil size and image quality that accompany the accommodative response. Methods: Using a high resolution Shack-Hartmann aberrometer, we measured refractive state as a binocularly viewed 0.30 logMAR (6/12 or 20/40) letter E was moved from 2 m to 20 cm and simultaneously monitored pupil diameter and spherical aberration for 19 subjects (mean age: 42 AE 7.18 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…Studies assessing the effect of pupil size in pseudophakic visual performance tend to use a single measure of the pupil size performed monocularly with a pupillometer [22]. There are some important limitations in this approach with respect to visual assessment conditions since it accounts for neither binocularity nor object distance [23,24]. Recently, Almutairi et al [24] reported an average pupil decrease of 0.24 mm/D of stimulus vergence, in different age groups, including full presbyopes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies assessing the effect of pupil size in pseudophakic visual performance tend to use a single measure of the pupil size performed monocularly with a pupillometer [22]. There are some important limitations in this approach with respect to visual assessment conditions since it accounts for neither binocularity nor object distance [23,24]. Recently, Almutairi et al [24] reported an average pupil decrease of 0.24 mm/D of stimulus vergence, in different age groups, including full presbyopes.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the between subject accommodative response SDs with bilateral distance correction increased from 0.24 D before the response to 0.48 D after the 2.00 D far‐to‐near response. This increase is primarily due to between subject differences in accommodative response amplitudes (ranging from 0.40 D to 1.90 D, as anticipated in this age group …”
Section: Resultsmentioning
confidence: 96%
“…Both measures of refractive state were employed because estimates of accommodative response amplitude depend on the pupil weight used to determine refractive state . Measured refractive state at the spectacle plane was converted to the eye's entrance pupil plane using standard paraxial transfer equations and normalised to the refractive state required to focus the distant 2 m stimulus . Image quality was quantified using the AreaMTF metric, which unlike Strehl ratio based metrics, provides meaningful estimates of image quality in the presence of up to 2.00 D of defocus .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…measure these changes in slope using an objective double‐pass system and find that in younger adults the slope remains almost constant up to the age of 35 and declines steadily thereafter. Almutairi et al . also measure the response/stimulus curve, together with the pupil diameter, of subjects between the ages 27 and 60 years.…”
Section: Changes In Refraction and Accommodation Performance With Agementioning
confidence: 99%